COMPARING THE TOXIC EFFECTS OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS (CELECOXIB AND IBUPROFEN) ON HEART, LIVER, AND KIDNEY IN RATS - Aziz, Noor D; Ouda, Mazin H.; Ubaid, Moayad Mijbil (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Nonsteroidal anti-inflammatory drugs (NSAIDs) do not reverse the disease progression, but they provide relief from pain and inflammation by inhibiting cyclooxygenase (COX) enzymes mediating the inflammatory pathway. Our aim was to make a meaningful comparison of both selective and non-selective COX-2 inhibitor to evaluate their toxic effects by measuring biochemical and histological alterations of heart, liver, and kidney. Methods: This study was conducted on 18 Sprague-Dawley rats of both sexes for 30 days, rats were divided into three groups (control group, ibuprofen group, and celecoxib group) each group included six rats. Results: The results are revealed that serum level of alanine aminotransferase, aspartate aminotransferase, alkaline phosphates, and total serum bilirubin was significantly increased (p<0.05) in ibuprofen and celecoxib group when compared with control, the highest level in celecoxib group, also serum level of urea was significantly elevated (p<0.05) in ibuprofen group when compared with control and celecoxib groups. Histopathological changes in cardiac tissue represented by vascular congestion and pericardial infiltration which are more prominent in celecoxib group, the changes in liver tissue revealed by vascular congestion and mild portal tract inflammation which is chronic in celecoxib group, while histological alterations in kidney tissue represented by severe vascular congestion with tubular necrosis which is more prominent in ibuprofen group. Conclusion: Both ibuprofen and celecoxib group have toxic effects on heart, liver, and kidney represented by the biochemical and histopathological findings.